Centers of the Urban Environment / Survival of the Cities - Gruen Victor (Van Nostrand Reinhold, 1973)
Foreword, Horizons and Restraints, The Regional Sopping Center - Its Contribution to Environmental Planning, Tenty Years: Shopping Towns International, The Unifunctional Centre - Its Rise and the Downfall of Urbanism, The Multifunctional Centre, Urban Cores, The Emerging New Urban Pattern, Summary, Index.